Nuclear medicine physics - Lima, J. J. Pedroso de (Joao Jose Pedroso). (Boca Raton, CA. : CRC Press, 2011)
'Edited by a renown international expert in the field, Nuclear Medicine Physics presents a full description of nuclear medicine imaging physics and methodology, serving as a useful reference of the basic physics and various applications in medicine and imaging systems. Written at a level accessible for a wide audience, including graduate students, this book provides advanced knowledge of relevant physical aspects behind modern nuclear imaging techniques, from radioisotope production to data acquisition and processing. Special emphasis is placed on the physics of biological functions from the perspective of their study with radioisotopes and the biological effects of radiation'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Medical physics; Radioisotope scanning